PEMBELAJARAN PECAHAN DENGAN MEDIA BAHAN MANIPULATIF - Hartatiana, Hartatiana (Al 'Ilmi : Jurnal Pendidikan MIPA, 2012)
Mathematics is a univeral saence that underlies the derhpment of modent  technology, it has an imporlant rulein avariety of lisapirnes and advansce the human intelled. To master and create technologies  in the future need strongs math master early  on. Mathematics courses should be given to all students ranging form elementary school to equip students with the ability to think logically, analytica, systematic, critlica and crative, as well as the ability to coopelute. These capabilities can be obtained throigh the process ofplanmn implementing and evaluasi good learning evaluation. In the implementation, besides appronate method also niquired the use of appropiiate media which one of the psapose is in onler to the abstract concept of mathematics is shown in form of concrete. So that it is understanable. In learning fraction the feather can use manipulative materials from paper as alternatir media. Throub this media, the students are expected to manpulative, so the concept presented easier to understand.